Anterior cruciate ligament rupture - exploring mechanism of healing and its impact in different treatment methods - Tomicka, Ewa; Czapiński, Olgierd; Zięba, Natalia; Ciesielski, Maciej; Kuś, Justyna; Pysiewicz, Mateusz; Białowąs, Patrycja; Knapik, Anna; Brodowska, Anna (Quality in Sport, 2026)
Anterior cruciate ligament (ACL) is one of the primary stabilizers of the knee joint, preventing anterior tibial translation and contributing to rotational stability. ACL rupture is among the most common injuries in young athletes, although it may occur in individuals of any age. In recent years, the incidence of ACL injuries has increased due to greater participation in sports and physically active lifestyles, leading to growing demand for effective treatment methods. Currently, anterior cruciate ligament reconstruction (ACLR) is considered the standard treatment approach. The procedure typically uses autografts harvested from the patient’s own tendons, although allografts and synthetic ligaments may also be utilized. Advances in the understanding of ligament biology and healing mechanisms have contributed to the development of newer primary repair techniques aimed at preserving native ACL tissue and proprioceptive function while reducing donor-site morbidity and enabling earlier rehabilitation. Although ACLR has been extensively studied and refined over decades, newer repair methods still require further long-term clinical evaluation. Each treatment strategy presents specific advantages and limitations, and none completely eliminates the risk of graft failure or post-traumatic osteoarthritis. This review summarizes the biological phases of ACL healing and discusses current treatment options in relation to these processes.